The Use of Fish Flour and Palm Sugar Medium to Grow Mataram Indigenous Isolate of Entomopathogenic Bacillus thuringiensis for Controlling Aedes agypti Larvae - Bambang Fajar Suryadi; Hilal Aisyah Hidayat; Galuh Tresnani (Journal of Tropical Life Science, 2019)
To grow Mataram indigenous local isolate of entomopathonic Bacillus thuringiensis using 4 combinations of fish flour and palm sugar natural liquid medium. The culture was then tested against 3rd instar Aedes aegypti larvae to gain lethal concentration (LC) value within 72-hour test. Four combinations of fish flour and palm sugar liquid medium (in 1:1; 1:3; 1:5 and 1:7 weight ratio) were made to grow B. thuringiensis isolate Bt-TP2B. Cell, endospore and protein crystal were recorded every 24 hours within 72-hour incubation. Seventy-two-hour-old B. thuringiensis cultures from those media were serially diluted, then tested against 3rd instar B. thuringiensis larvae. Larval death was recorded every 24 hours within 72-hour observation to obtain lethal concentration (LC) values. Results from all medium were compared to those of NYSM standar medium. B. thuringiensis isolate BT-TP2B could grow in fish flour and palm sugar natural medium. The highest toxicity (the lowest LC) was seen on B. thuringiensis grown on fish flour and palm sugar natural medium in 1:1 weight ratio. The LC50 values were 1.98x103 cell/mL (in 24-hour observation) and 1.49x103 cell/mL (in 48-hour and 72-hour observation), while LC90 values were 1.35x103 cell/mL in 24-hour observation and 1.58x103 cell/mL in 48 and 72-hour observations). These values were lower (more toxic) compared to those of NYSM standard medium. Fish flour and palm sugar natural medium could be used to grow entomopathogenic B. thuringiensis. Moreover, this natural medium could increase toxicity of B. thuringiensis against B. thuringiensis3rd instar larvae.Â